Future-Proof Doctrine or Relic of an Equitable Past? Unconscionable Conduct in the Fair Trading Amendment Act 2021 - Chan, Sean (Victoria University of Wellington Law Review, 2022)
The Fair Trading Amendment Act 2021 introduced a New Zealand prohibition on "unconscionable conduct" in trade. Previously, the law on unconscionable conduct was found in the equitable doctrine of unconscionable bargain. This article describes how New Zealand law has moved away from equitable unconscionability with this new prohibition. This article critically analyses some of the legal, social and economic justifications for introducing the prohibition, finding that some of the Ministry of Business, Innovation and Employment's justifications are not persuasive. The s 7 prohibition is based strongly on an equivalent section in the Australian Competition and Consumer Act 2010 (Cth). It is argued that long-standing doctrinal issues with Australia's prohibition provided a strong basis for New Zealand to pursue a different standard. Finally, this article explores the "unfair commercial practices" doctrines in the United States and European Union through the lens of anti-consumer practices in digital marketplaces. The conclusion is that the unfair commercial practices doctrine captures a wider range of anti-consumer conduct than does unconscionable conduct.